PENGARUH PENGELOLAAN KELAS TERHADAP PRESTASI BELAJAR SISWA DI SDN 2 WERU KIDUL KABUPATEN CIREBON - khaerunnisa; Labudasari, Erna (EDUTARY (Education of Elementary School), 2025)
The objectives of this study are (1) To know and explain the management of classes in Weru Kidul 2 Elementary School, (2) To describe how student learning achievements, (3) To measure the effect of class management on the learning achievement of SD N 2 Weru Kidul students at Weru District, Cirebon Regency. The population in this study are students of SD N 2 Weru Kidul, Plered District, Cirebon Regency. The research sample involves students from grade 1 to 6 by randomly taking 6 students from each class. Based on the results of the liliefors normality test, both of the class management variable data (X) and learning achievement (Y) are normally distributed, then seen from the linearity test the data variable x to the y variable indicates the value of sig. 27.6%> 5% and F count 1.325 < 2.230 and the data on the y variable on the x variable show sig values. 95.6%> 5% F count 0.427 <2.230 which means that data is considered linear. Furthermore, it can be seen from the correlation test, the data shows a coefficient of determination of 1.3%, which means that student learning achievement data (Y) can be explained by class management (X). After that, a regression test is performed which showed that the t count of data is 1.737 bigger than the t table of 1.684 which means that Ho is rejected and Ha is accepted.